ChemInform Abstract: Chromogenic and Fluorogenic Chemosensors and Reagents for Anions. A Comprehensive Review of the Years 2010—2011. Issue 25 (3rd June 2013) - Santos‐Figueroa, Luis E.; Moragues, Maria E.; Climent, Estela; Agostini, Alessandro; Martinez‐Manez, Ramon; Sancenon, Felix
Abstract Review: 359 refs.